PERAN DANA TRANSFER KHUSUS BAGI PEMBANGUNAN BIDANG IRIGASI PASCABENCANA PROVINSI SULAWESI TENGAH - Andi Setyo Pambudi; Bambang Pramujo (Jurnal Kebijakan Pemerintahan, 2022)
Abstract Irrigation is an important part of achieving food security, affecting the community's social and economic aspects. The food sector still occupies a strategic role in Indonesia in supporting the achievement of national development that affects the economic growth rate. Funding for irrigation involves the state budget (APBN) and local government budget (APBD), including special transfer funds for priority areas. Presidential Regulation No. 72/2018 concerning RKP 2019 stipulates the purpose of implementing the Physical DAK for the Assignment of the Irrigation Sector to assist the regions in carrying out the development (improvement and rehabilitation) of irrigation infrastructure which is the regional authority to contribute to the achievement of the Food Sovereignty agenda. The disaster in Central Sulawesi in 2018 had an impact on the water resources infrastructure in the region. Problems in implementing the Physical DAK need to be explored as input for future DAK planning, especially for the irrigation sector. Given the importance of the Physical DAK related to irrigation for local governments in Central Sulawesi, it is interesting to analyze the role of DAK and explore problems in its implementation in the context of regional development. This study aims to elaborate on the role of the Physical DAK in developing the irrigation sector in the regions and analyze the problems that occurred during its implementation. The method used is a literature study and field visits (discussions) with regional development stakeholders. The study results indicate that there is not yet complete alignment between national priorities related to irrigation and regional needs. In practice, the issue of disaster has become a consideration for the allocation of the DAK budget, and this has occurred in the Province of Central Sulawesi. However, it must be acknowledged that strengthening the irrigation sector with a logical framework and appropriate risk management continues to be encouraged with special transfer funds to accelerate development targets that are better and beneficial to the post-disaster community. Keywords: DAK, Disaster Rehabilitation, Irrigation, National Priorities, Regional Development